Microgrid stabilization using controllable electrolyzer & fuel cell based on bee colony optimization of fuzzy-pid controller - Chaiyatham, Theerawut; Ngamroo, Issarachai (My University, 2010)
Due to the intermittent power generations from wind and photovoltaic in the microgrid, these result in the power fluctuation. To suppress power fluctuation, the coordinated controls of aqua electrolyzer (AE) and fuel cell (FC) can be applied as the controllable distributed generations. In this paper, a bee colony optimization (BCO) is proposed to design the optimal fuzzy logic based-proportional-integral-derivative (FLPID) controller of AE and FC. Without trial and error as in the conventional FLPID controller design, scale factors, membership functions and control rules of the optimal FLPID controller are automatically and simultaneously tuned by the BCO. Simulation results confirm the superior effect of the proposed optimal FLPID controller in comparison with the conventional FLPID controller.
Keywords: Aqua electrolyzer; Bee colony optimization; Fuel cell; Fuzzy logic-PID controller; Microgrid